Quantitative Risk-Based Inspection on Gas Riser Pipelines at Offshore Facilities - Asfar, Mhd. Ibkar Yusran; Soedarsono, Johny Wahyuadi; Wijaya, Arie; Aditiyawarman, Taufik; Soelistiyono, Dony; Ramadhan, Romal (Teknomekanik, 2021)
Numerous pipeline failures have occurred due to the drastic increase in oil and gas product distribution pipelines over the last three decades. Corrosion is a significant factor in the failure of offshore gas pipelines. It is necessary to maintain the integrity of the offshore transmission system, one of which is the riser, for the product to be adequately distributed. The purpose of this study is to ensure the riser's reliability by conducting a risk assessment of the probability and consequences of equipment failure, mitigating the impact of failure risk, and developing a more optimal inspection plan. The API 5L Grade X60 gas riser pipe is the subject of this study. The quantitative Risk-Based Inspection (RBI) technique was used in 2016 following the API 581 standard. This quantitative approach is founded on a numerical value model constructed using validated operational data and inspection results. The risk assessment indicates that the gas riser pipelines will have a high-risk level (5D) for the splash zone segment and a medium-risk level (2D) for the above-and below-water segments. The recommended inspection plan for the gas riser pipeline is one year after the risk-based inspection assessment.